Secondary Geodiversity and its Potential for Urban Geotourism: A Case Study from Brno City, Czech Republic - Kubalíková, Lucie; Kirchner, Karel; Bajer, Aleš (Quaestiones Geographicae, 2017)
Secondary geodiversity (represented by anthropogenic landforms, which can be considered a significant part of geoheritage of certain area) can be seen as an important resource for geotourism and geoeducational activities within urban areas. Brno city (Czech Republic) is rich in these landforms as well as numerous urban areas. Some of them (especially old quarries and underground spaces) are already used for recreation, tourism and leisure or they serve as excursion localities for the university students, some of them are unique from the geoscience point of view and they have also certain added values (historical, archaeological or ecological). However, in some cases, their potential is not fully recognised. The article describes the main anthropogenic landforms within Brno city and analyses their suitability for geotourism and geoeducational activities.